THE MEDIATING ROLE OF EMPLOYEE RETENTION ON THE INFLUENCE OF LEADERSHIP STYLE AND TALENT MANAGEMENT ON EMPLOYEE PERFORMANCE AT PT PLN (PERSERO) UNIT INDUK DISTRIBUSI EAST JAVA - Hanggara, Mirza Putra; Suswati, Endang; Martaleni, Martaleni; Wijayanti, Tri Cicik (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of leadership style and talent management on employee performance with employee retention as a mediating variable at PT. PLN (Persero) Unit Induk Distribusi Jawa Timur. A quantitative approach with explanatory research design was employed. Data were collected through questionnaires distributed to 160 employees using a saturated sampling technique. Data analysis was conducted using SEM-PLS. The results show that (1) leadership style has a positive and significant effect on employee performance, (2) talent management has a positive and significant effect on employee performance, (3) employee retention significantly improves performance, (4) leadership positively affects employee retention, (5) talent management positively affects employee retention, (6) retention mediates the relationship between leadership and performance, and (7) retention mediates the relationship between talent management and performance. The study provides theoretical implications regarding the mediating role of retention and practical recommendations for PLN’s management to strengthen leadership effectiveness and talent strategies.